(untitled) (African Journal of Geographical Science, 2020)
This study was carried out to determine the relationship between environmental awareness and attitude among secondary school students. A total of 240 respondents who were in senior secondary schools in Ijebu-North local government area of Ogun State, constituted the sample. A questionnaire instrument which contained 35 items was employed to collect the data. The results of Pearson Correlation analysis showed a significant but low relationship between environmental awareness and environmental attitude of the students. Furthermore, the t-test statistical analysis conducted on difference in environmental awareness and attitude based on gender, age and class showed that there is no difference in the environmental awareness and attitude of respondents by gender, age and class. The study recommended that environmental education should be considered as a school subject in the Nigerian education system.